Pelatihan Desain Grafis untuk Meningkatkan Kreatifitas dan Menambah Daya Saing Masyarakat Kecamatan Pasar Minggu Jakarta Selatan - Ridwan Raafi'udin; Bayu Hananto; Catur Nugrahaeni Puspita Dewi (SULUH: Jurnal Abdimas, 2020)
The availability of information and communication technology (ICT) has made it a lot of convenience in everything. An example is the existence of online trading transactions, for we can market these products online both through marketplaces and social media, we must-have products that are slightly different from the others. One way is to design your own product packaging that we will sell, and for example it can be started by making a product logo. This is the basis of community service activities, and this activity utilizes the creative side of partners so that they can create a design that will be packaged in the next stage in the form of merchandise. In this design training phase, partner participants were given the understanding to use vector-based graphic design applications, from creating product logos to digital advertising posters